Reviews - Aaby, Bent; Kaul, Flemming; Becker, C.J.; Axboe, Morten (Journal of Danish Archaeology, 1993)
Reviews: F.M. CHAMBERS (ed.): Climate Change and Human Impact on the Landscape (by Bent Aaby). B. E. BERGLUND (ed.): The Cultural Landscape during 6000 Years in Southern Sweden (by Bent Aaby). J.L. DAVIDSON & A.S. HENSHALL: The Chambered Cairns of Orkney. J.L. DAVIDSON & A.S. HENSHALL: The Chambered Cairns of Caithness. N. SHARPLES & A. SHERIDAN (eds.): Vessels for the Ancestors (by Flemming Kaul). VIGGO NIELSEN: Jernalderrens Pløjning. Store Vildmose (by C.J. Becker). MARTIN CARVER (ed.): The Age of Sutton Hoo (by Morten Axboe).